Classroom Techniques Used by English Teacher in Inquiry Based Learning: Naturalistic Study at SMP Negeri 2 Karanganom - Ningsih, Sinta Putri; , Prof. Dr. Endang Fauziati, M. Hum (2017)
This study aims at describing classroom techniques used by English teachers in inquiry based learning at SMP Negeri 2 Karanganom. The type of this research is descriptive qualitative research especially naturalistic study. The methods of collecting data in this research are observation, interview, and document. The results of the research show that there are twelve classroom techniques used by English teachers in inquiry based learning at SMP Negeri 2 ranganom, such as: reviewing the previous lesson and over viewing the new lesson in the exploration stage, question and answer exercise, choral imitation, translation, transformation, elicitation, reading aloud, song and rhymes, correction, dictation in elaboration stage and summarizinginconfirmation stage. Each of the classroom techniques has objectives. There are materials used by English teacher, such as English textbook and dictionary. The roles of the instructional materials are as a source of activities for learners’ practices and communicative interaction, a source of stimulation and ideas for classroom language activities, a reference source for learners on grammar, vocabulary, pronunciation, and so on. The teachers in SMP Negeri 2 Karanganom have roles as motivator and manager in exploration stage, inquiry controller and facilitator in elaboration stage and as explainer in confirmation stage. The students also have roles as active learner and participant in exploration stage, as learner from other teaching sources, active learner, monitor and evaluator, and participant in elaboration stage, and as learner from the teacher and participant in confirmation stage. The esearcher concludes that English teachers at SMP Negeri 2 Karanganom used several techniques which can develop the students’ English skill. Various classroom techniques can make the students more interested and enthusiastic in teaching learning process. It lets the students to understand the material easily.